2022
DOI: 10.1177/13540688211069544
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between party polarization and citizen polarization

Abstract: Do party policy offerings simply reflect public opinion or do parties shape public demand for policies? Theories of party position-taking and the operation of democracy expect parties to track their supporters’ positions, while scholarship of public opinion has shown voters often adopt the position of their preferred parties. We apply both of these theoretical expectations to the relationship between citizen polarization and party polarization and additionally argue that the relationship between them should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…This suggests that elite polarization can influence polarization among ordinary citizens. Moral and Best (2023) show that the causal arrow generally runs from elite polarization to mass polarization, with the largest and most immediate effects among the most politically sophisticated citizens. However, his study focused on ideological rather than affective polarization, so further research is required in this matter.…”
Section: Objection 3: What If CV Increases Other Forms Of Political P...mentioning
confidence: 94%
“…This suggests that elite polarization can influence polarization among ordinary citizens. Moral and Best (2023) show that the causal arrow generally runs from elite polarization to mass polarization, with the largest and most immediate effects among the most politically sophisticated citizens. However, his study focused on ideological rather than affective polarization, so further research is required in this matter.…”
Section: Objection 3: What If CV Increases Other Forms Of Political P...mentioning
confidence: 94%
“…This follows the demand-side logic of electoral politics: parties are responsive to changes in public opinion, so if the public becomes more polarized, then parties will follow in turn (e.g., Budge et al, 2012). Many studies have provided evidence for party responsiveness to changes in voter preferences (Adams et al, 2004, 2006; McDonald and Budge, 2005; Ezrow and Xezonakis, 2011; Ezrow et al, 2014), although this effect does not appear to extend to party polarization (Moral and Best, 2022). At the meso-level, party polarization is often attributed to institutional factors, such as the proportionality of the electoral system (Downs, 1957; Cox, 1990; Calvo and Hellwig, 2011; Dow, 2011), whether parties are in government or in opposition (Bawn and Somer-Topcu, 2012), and coalition expectations (Curini and Hino, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Studies of the United Kingdom have found modest convergence among the public, but people who perceived convergence among parties followed suit (Adams et al, 2011; Adams etal., 2012). In a recent study of 19 advanced democracies, Moral and Best (2022) find that citizens, especially informed and engaged ones, follow political parties as they become more or less polarized (and that this effect does not occur the other way around).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations